Molecular Identification of Mycobacterium tuberculosis and Analysis of Its Resistance to Rifampin in Sputa From Tuberculosis Suspected Patients - M. Syaifudin (Atom Indonesia, 2010)
An accurate identification of different species of Mycobacterium provides to allow appropriate treatment for Mycobacterium tuberculosis infection. Beside that, drug resistance of M. tuberculosis strains to rifampin is not clearly understood in contributing to the spread of tuberculosis in Indonesia. To assess the molecular mechanism of rifampin resistance, a number of clinical specimens of M. tuberculosis were analyzed their molecular nature of a part of the rpoB gene using polymerase chain reaction-single strand conformation polymorphism (PCR-SSCP) methods. DNA’s extracted from sputum samples were amplified and 32P-labeled by PCR with the specific primers and the product was analyzed their mutation conferring resistance by MDE gel electrophoresis. Of the 70 specimens tested, 57 specimens were positive for M. tuberculosis organism only, three specimens contained a mixture of M. tuberculosis and non tuberculosis mycobacteria (NTM), and 10 specimens were negative approved by Duplex PCR. Of these sixty DNA positive samples (thus the sensitivity of PCR was 85.71%), 5 (8.3%) of them suspected to contain mutations in rpoB which were associated with rifampin resistance. Even though the frequency of mutation was low, the results from our study clearly indicate that the molecular mechanism of rifampin resistance in M. tuberculosis isolates from Indonesia involves alterations in the rpoB gene. Molecular diagnosis by PCR which is fast and easy to perform is useful for early and rapid detection of TB in sputum specimen. Received: 27 February 2009; Revised: 28 August 2010; Accepted: 30 August 2010